Comparison analysis of the behaviour of rockfill dams with clay core at the variation of the water level in the reservoir - Petkovski L., Mitovski S. (United States Society on Dams, 2017)
By application of advanced numerical methods, the behaviour of embankment dams is successfully analyzed, almost for all typical states of static loading. The occurrences, not fully clarified during the static analysis of some types of embankment dams, are caused by the water effect. Such occurrences include: (a) hydraulic fracturing phenomenon of the coherent material (earth dams and earth-rock dams) during full reservoir with established steady seepage and (b) appearance of softening and weakening (or the latest term collapse settlement) of the rock material at the upstream dam shell in case of rock-fill dams with core, during the rapid filling of the reservoir. The topic of the research, whose results are included in the paper, is clarification of the stress-strain state for rock-fill dams with central waterproof element at variation of the water level in the reservoir. This issue, stated in the dam engineering in 70’s of the last century, was analyzed in several occasions, but the general conclusion is that the effect of water saturation of the rock material is not fully explained. In this paper are presented results from the comparison analysis of the variation of the water level of the reservoir, formed by construction of Kozjak Dam, on the river Treska, a tributary of the river Vardar. It is a rock-fill dam with slightly inclined clay core, with structural height of 129.0 m, the highest dam in the Republic of Macedonia. The first filling of the reservoir took place in 2003-2004 and the dam behaviour was monitored by surveying methods and by installed instruments in the dam body.